THE EFFECT OF PROBLEM BASED LEARNING MODEL ON CRITICAL THINKING ABILITY AND LEARNING OUTCOMES IN PLUIT RAYA SMK STUDENTS - Putri, Laras Widyas; Karyaningsih, RR Ponco Dewi; Munawaroh (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the effect of the problem-based learning model on critical thinking skills and student learning outcomes at SMK Pluit Raya. This research was conducted using a questionnaire research method with a sample of 161 students and the sampling technique was proportional random sampling. The data were analyzed using a simple linear regression technique to test the validity and reliability. From the results of the research conducted, it shows that problem based learning has a positive and significant effect on critical thinking skills and learning outcomes. Thus, teachers are expected to be able to apply problem-based learning models on an ongoing basis to improve critical thinking skills and student learning outcomes.